The mexican potato species Solanum neoantipoviczii BUK. (= S. stoloniferum Schlechtd.) from the taxonomic series Longipedicellata BUK. and its use in interspecific hybridization - N. M. Zoteyeva; Yu. Tarwacka (Труды по прикладной ботанике, генетике и селекции)
Background. There are more than 200 tuber-bearing species in the genus Solanum L. Many of them possess valuable traits able to improve some characteristics in present-day potato cultivars. Wild potato species have formed an entire ploidy series ranging from diploid to hexaploid. Many wild species have not yet been used in potato breeding. A barrier exists in crosses due to differences in chromosome numbers and EBN of parental species. In our previous evaluation of the accession S. neoantipoviczii Buk. VIR k-8505 was found to be highly resistant to Phytophthora infestans and to tree strains of Potato Virus Y (PVY) conferring resistance through the gene Rysto. In J. Hawkes's monography this species is mentioned as synonymous to S. stoloniferum Schlechtd. Russian taxonomist S. M. Bukasov recognized it as an independent species. At the same time D. Correll hypothesized that this species is the hybrid between tetraploid S. stoloniferum and diploid S. verrucosum Schlechtd. We counted the chromosome number in thirty seedlings of the accession S. neoantipoviczii k-8505 and studied the crossability of this accession in combinations with several other species.Material and methods. The plants of the species: S. neoantipoviczii Buk (female parent), original hybrid S. microdontum Bitt. x S. tarijense Hawk., S. berthaultii Hawk., S. ruiz-ceballosii Card., S. kurtzianum Bitt. et Wittm., S. papita Rydb., S. phureja Juz. et Buk. and S. tuberosum L. (male parents) differing in chromosome numbers and previously studied for useful traits were included in hybridization. The chromosome counting was performed in meristem root cells, extracted from in vitro plants. Hybridization was performed using cut branches of female parents after bud decapitation.Results and conclusions. Plants of the accession S. neoantipoviczii k-8505 were basically found tetraploid. In the crosses of S. neoantipoviczii used as the female parent, seeds were obtained in combinations with the accessions of wild (S. berthaultii, S. kurtzianum, S. papita, S. ruiz-ceballosii, hybrid S. microdontum x S. tarijense) and cultivated (S. phureja, S. tuberosum) potato species. Low seed numbers were recorded in the crosses with S. kurtzianum and S. berthaultii. In crosses with the other species, the seed number varied from 50.4 to 106.6.